Internal consistency of the Strengths and Difficulties Questionnaire in Amazonian children - Giacomini, Isabel; Martins, Maria Rosário O.; Matijasevich, Alicia; Cardoso, Marly A. (Revista de Saúde Pública, 2023)
OBJECTIVE: To describe the frequency of behavioral problems and the internal consistency of the parent version of the Strengths and Difficulties Questionnaire (SDQ-P) in Amazonian preschool children during the covid-19 pandemic.METHODS: Data from the Maternal and Child Health and Nutrition in Acre (MINA-Brazil) study, a population-based birth cohort in the Western Brazilian Amazon, were used. The SDQ-P was applied in 2021 at the five-year follow-up visit to parents or caregivers of 695 children (49.4% of which were girls). This instrument is a short behavioral screening questionnaire composed of 25 items reorganized into five subscales: emotional symptoms, conduct problems, hyperactivity/inattention, peer relationship problems, and prosocial behavior. Cases of behavioral problems were defined according to the original SDQ cut-offs based on United Kingdom norms. Moreover, cut off points were estimated based on the SDQ-P percentile results of our study sample. Internal consistency was assessed by calculating Cronbach’s alpha coefficient and McDonald’s omega for each scale.RESULTS: According to the cut-offs based on our studied population distribution, 10% of all children had high or very high total difficulty scores, whereas it was almost twice when the original SDQ cut-offs based on United Kingdom norms, were applied (18%). Differences were also observed in the other scales. Compared to girls, boys showed higher means of externalizing problem and lower means of prosocial behavior. The five-factor model showed a moderate internal consistency of the items for all scales (0.60 ≤ α ≤ 0.40), except for total difficulty scores, which it considered substantial (α > 0.61).CONCLUSIONS: Our results support the usefulness of SDQ in our study population and reinforce the need for strategies and policy development for mental health care in early life in the Amazon.